Effect of butyrate sources in a high-concentrate diet on rumen structure and function in growing rams - S. Świerk; M. Przybyło; J. Flaga; K. Szczepanik; W. Białek; P. Flieger; P. Górka (Animal, 2024)
Dietary butyrate is considered to have mostly positive impacts on the ruminal epithelium. However, its supplementation in a high-concentrate diet may not be justified as excessive ruminal butyrate may negatively affect the rumen. Furthermore, butyrate impact on the rumen may depend on its source. Thirty-two Świniarka growing rams (30.6 ± 2.5 kg; 11–14 months of age) were used to investigate the effect of a high-concentrate diet and sodium butyrate (SB) or tributyrin (TB) supplementation in a high-concentrate diet on the rumen structure and selected functions. The rams were allocated to four treatments and fed diets with: (1) low concentrate inclusion (22.5% of diet DM; L); (2) high concentrate inclusion (60% of diet DM; H); (3) H with SB (3.2% of diet DM; H+SB); and (4) H with TB (2.93% of diet DM; H+TB). The preplanned contrasts were used for treatment comparisons (L vs H treatments (H, H+SB, and H+TB), H vs H+SB, and H vs H+TB). The BW, BW gain and DM intake did not differ between treatments. In the atrium ruminis, epithelium thickness did not differ between the L and H treatments (P = 0.46), tended to be higher for H+SB than for H (P = 0.09) but did not differ between H+TB and H (P = 0.61). The expression of downregulated in adenoma was higher for L than for H treatments (P = 0.03) but was not affected by SB or TB supplementation (P ≥ 0.26). In the ventral rumen, the mucosa surface and epithelium thickness were lower for L than for H treatments (P < 0.01), were or tended to be higher for H+SB than for H (P ≤ 0.06) but did not differ between H+TB and H (P ≥ 0.26). The expression of monocarboxylate transporter 1 was lower for L than for H treatments (P = 0.02) but was not affected by SB or TB supplementation (P ≥ 0.28). The expression of putative anion transporter-1 and downregulated in adenoma did not differ between the L and H treatments (P ≥ 0.76); however, expression of the former tended to be higher and the latter tended to be lower for H+SB than for H (P ≤ 0.09), whereas no differences were observed between H+TB and H (P ≥ 0.14). In summary, SB supplementation, but not TB supplementation, in a high-concentrate diet stimulated ruminal epithelium growth and affected short-chain fatty acid transporters expression in the ruminal epithelium.